Training on Preparing Company Financial Position Reports - Sufiyati Sufiyati; Melvin Vanwi Goenawan; Eric Bryan Lie (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2025)
Backgrounds: Accounting plays a vital role in recording business transactions and documenting a company’s assets and financial position. Financial statements are essential tools for presenting a company’s financial condition, with the statement of financial position providing a snapshot of assets, liabilities, and equity at a specific point in time. However, high school students often have limited understanding of this report, which can hinder their financial literacy and readiness for further education or practical application. Objectives: This training activity aimed to enhance accounting knowledge related to the preparation and understanding of the statement of financial position among grade XII students at SMA Kristoforus 1. Methodology: The training was conducted through face-to-face sessions in October 2025. The program began with identifying partner needs, particularly students’ limited comprehension of the statement of financial position. The teaching team designed interactive training sessions supported by structured modules, theoretical explanations, sample problems, group exercises, discussions, and quizzes to assess understanding. Findings: Students showed high levels of enthusiasm and active participation throughout the training, including asking questions and engaging in discussions. Quiz results demonstrated a significant improvement in students’ understanding of the statement of financial position, indicating that the training effectively strengthened their accounting comprehension. Conclusions: The training program proved effective in improving students’ understanding of the statement of financial position and enhancing their financial literacy. Interactive learning methods and practical exercises were key factors contributing to the success of the activity, suggesting that similar approaches can be applied to accounting education at the secondary school level.